2016
DOI: 10.1089/brain.2015.0405
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric Dorsolateral Prefrontal Cortex Connectivity is Associated with Individual Differences in Pain Sensitivity in Healthy Controls

Abstract: The dorsolateral prefrontal cortex (DLPFC) is implicated in pain modulation through multiple psychological processes. Recent noninvasive brain stimulation studies suggest that interhemispheric DLPFC connectivity influences pain tolerance and discomfort by altering interhemispheric inhibition. The structure and role of interhemispheric DLPFC connectivity in pain processing have not been investigated. The present study used dynamic causal modeling (DCM) for fMRI to investigate transcallosal DLPFC connectivity du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 42 publications
1
31
3
Order By: Relevance
“…In fact, other neuromodulation studies have also claimed that DLPFC is involved in modulating emotional-affective experience of pain, which represents individual's tolerance to pain (GraffGuerrero et al, 2005;Mylius et al, 2009). A recent fMRI study demonstrated that greater connectivity between bilateral DLPFCs was associated with higher heat pain thresholds (Sevel et al, 2016). These findings taken together highlight the role of DLPFC in pain modulation, particularly pain tolerance.…”
Section: Correlation Of Fc Changes To Individual Baseline Pain Threshmentioning
confidence: 86%
“…In fact, other neuromodulation studies have also claimed that DLPFC is involved in modulating emotional-affective experience of pain, which represents individual's tolerance to pain (GraffGuerrero et al, 2005;Mylius et al, 2009). A recent fMRI study demonstrated that greater connectivity between bilateral DLPFCs was associated with higher heat pain thresholds (Sevel et al, 2016). These findings taken together highlight the role of DLPFC in pain modulation, particularly pain tolerance.…”
Section: Correlation Of Fc Changes To Individual Baseline Pain Threshmentioning
confidence: 86%
“…In regard to the brain and pain, activation of the DLPFC is associated with cognitive decision making, including pain evaluations and response decisions, and is accomplished by modulation of the corticosubcortical and corticocortical pathways 36. Recent noninvasive brain stimulation studies have suggested that interhemispheric DLPFC connectivity influences pain tolerance and discomfort by altering interhemispheric inhibition,37 and these studies have also supported the preferential role of the right hemisphere in pain processing because of disrupted homotopic connectivity in the DLPFC 38. Microstructural abnormalities in the gray matter of the DLPFC provide a structural foundation for understanding the disruption in connectivity,5 as iFC is partially restored after pain treatment, which indicates that the DLPFC participates in cognitive task performance and also supports the concept that DLPFC connectivity participates in brain impairment during chronic pain 39.…”
Section: Discussionmentioning
confidence: 98%
“…In other words, the DLPFC suppressed insula and thalamus activity and reduced pain sensitization associated with uncontrollable pain. Finally, the connectivity between left and right DLPFC has been linked to individual pain sensitivity, such that stronger interhemispheric connectivity was associated with greater pain tolerance 93 .…”
Section: Dlpfc Functionmentioning
confidence: 99%